TOXICITY AND ANTIMICROBIAL ACTIVITY FROM EXTRACT AND OLEANAN DERIVATIVE COMPOUNDS OF THE BARK MELOCHIA UMBELLATE (HOUTT) STAPF VAR. DEGRABRATA - USMAN,; NUNUK HARIANI SOEKAMTO,; HANAPI USMAN,; AHYAR AHMAD, (International Journal of Pharma and Bio Sciences, 2014)
Oleanan derivative compound namely 3-acetyl-12-oleanen-28-oic acid, has been isolated from n-hexane fraction of the bark M. umbellate (Houtt) Stapf var. degrabrata The molecular structure was determined by IR spectroscopy, NMR 1D and 2D (1H-NMR, 13C-NMR, DEPT, COSY, HMQC and HMBC). The results of test bioactivity to hexane, chloroform, ethyl acetic, methanol extracts and compound 1 mentioned above showed that they are toxic to A. salina (brine shrimp) with LC50 361.93 to 460 µg/mL. The most toxic one was the compound 1 with the LC50 value of 361.93 µg/mL. At a concentration of 1000 µg/mL, the extract of hexane, methanol and compound 1 showed very high inhibition to the growth of B. subtilis and C.albican, whereas the extract of ethyl acetate had very high inhibition effect to the growth of S. aureus and A. niger. The inhibition zone of the three extracts and compound 1 were greater than 14 mm. On the other hand, the extracts of chloroform gave weak inhibition against bacteria and fungi.